2008
DOI: 10.1002/jsfa.3324
|View full text |Cite
|
Sign up to set email alerts
|

Food and feed components for gut health‐promoting adhesion of E. coli and Salmonella enterica

Abstract: BACKGROUND: A host runs less risk of contracting a gastrointestinal infection when enteropathogenic bacteria adhere to dietary fibers instead of to epithelial cell receptors. The aim of this study was to test the binding capacity of food and feed components for intestinal bacteria from various hosts using a miniaturized in vitro assay. In total, 18 dietary components were tested with four strains of E. coli, seven strains of Salmonella enterica and two strains of Lactobacillus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
2
22
0
1
Order By: Relevance
“…The reason that palm kernel meal requires more CFU compared to other feed materials is presently unknown. However, Becker and Galletti observed that palm kernel meal effectively adhered to Salmonella, possibly because of high levels of mannans (9). Consequently, these results suggest that regardless of the analytical procedure employed, Salmonella contamination rates for palm kernel meal are likely underestimated.…”
Section: Discussionmentioning
confidence: 93%
“…The reason that palm kernel meal requires more CFU compared to other feed materials is presently unknown. However, Becker and Galletti observed that palm kernel meal effectively adhered to Salmonella, possibly because of high levels of mannans (9). Consequently, these results suggest that regardless of the analytical procedure employed, Salmonella contamination rates for palm kernel meal are likely underestimated.…”
Section: Discussionmentioning
confidence: 93%
“…Ofek et al (2003a) describes that-apart from adhesion-receptor interaction-hydrophobic and other non-specific interactions might be involved in the adhesion process as well. Becker and Galletti (2008) investigated various food and feed components for alternative adhesion of intestinal E. coli and Salmonella. Yeast mannan oligosaccharides, pumpkin, sesame seed extract, palm kernel extract, and konjac gum were among the strongest binding matrices for enteropathogens.…”
Section: Mode(s) Of Action Anti-adhesion Approachmentioning
confidence: 99%
“…Thus, indication is given that unspecific, unknown binding properties are involved in this process. Moreover, taking the diversity of natural products due to biological variation for processing into account, the binding capacity of fibrous food and feed components for different bacteria seems rather unpredictable (Becker and Galletti 2008).…”
Section: Mode(s) Of Action Anti-adhesion Approachmentioning
confidence: 99%
“…MOS would also have an additional important antimicrobial effect based on their capacity to bind to mannose‐specific lectin of gram‐negative pathogens that express type‐1 fimbriae (Borowsky et al . ), thus blocking the adhesion of these bacteria to the enterocytes and preventing the subsequent colonization (Becker and Galletti ). This binding capacity may, however, be very variable because MOS come from a wide variety of sources (oil palm seeds, coffee beans, yeast, carob seeds, etc.…”
Section: Introductionmentioning
confidence: 99%